The death of asylum: hidden geographies of the enforcement archipelago - Mountz, Alison (University of Minnesota Press, 2020)
"Alison Mountz traces the global chain of remote detention centers used by states of the Global North to confine migrants fleeing violence and poverty, using cruel measures that, if unchecked, will lead to the death of asylum as an ethical ideal"--